Project Feasibility Study at waste management project (case study TPPAS Nambo) - Yulinda, Fany; Sumirat, Erman (The Indonesian Journal of Business Administration, 2013)
The Government of the West Java Province (represented by West Java Waste Management Agency – Badan Pengelola Sampah Regional (BPSR) Jawa Barat) overtaken such waste problem by arranging development plan of the Nambo recycling and final processing landfill - Tempat Pengolahan dan Pemrosesan Akhir Sampah Nambo (NAMBO TPPAS). This project are involved into the sanitation priority project in the Private-Public Partnership (PPP) – Kerjasama Pemerintah dan Swasta (KPS) scheme implemented altogether with BAPPENAS. Waste on Nambo TPPAS will be processed into useful products 1.Recycle Material 2. RDF(refuse derived fuel) 3. Compost. These projects are expected to be the solution to the waste problem in the city of Bogor and Depok. This Final Project is to analyze the project feasibility study of development projects nambo TPPAS based on Regulation of Minister of national development planning No.3 2012 . Feasibility study perform by using various indicators of financial feasibility including IRR,NPV and PBP, combined with Sensitivity Analysis, Risk Analysis , and ABMS (analisa Biaya manfaat sosial – Social cost benefit Analysis). Based on the analysis of financial and risk positions suggests that development projects can be assessed Nambo TPPAS feasible to be implemented with the assumption that the government provide support in the form of government funding in the beginning of the project. However, the project can’t be assessed only in terms of financial side but must be assessed in terms of the resulting social benefits. These projects generate substantial EIRR. This prompted the government to immediately implement the construction of this project. Keyword: Waste, Waste management, RDF , PPP , Project feasibility Study.